2019
DOI: 10.9745/ghsp-d-19-00117
|View full text |Cite
|
Sign up to set email alerts
|

Role of Male Sex Partners in HIV Risk of Adolescent Girls and Young Women in Mozambique

Abstract: Efforts to prevent HIV among adolescent girls and young women (AGYW) should focus on providing male sexual partners of AGYW with HIV prevention, testing, and treatment programming and providing AGYW, particularly those who are less educated, pregnant, or single mothers, with prevention methods that do not require negotiating safer sex with their partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
“…Community leaders saw DREAMS multi-sectoral approach as a lost opportunity to include young men who faced similar youth development challenges [26]. While young men have sexual reproductive health (SRH) needs and are partners of AGYW [26] in our community this ambivalence mirrored the well-described barriers to shifting gender-norms in South Africa [27][28][29]. DREAMS implemented a package that addressed gender-based violence explicitly and gender dynamics implicitly (contraception education and access, stepping stones and cash transfers).…”
Section: Youth Development Was Embraced By the Community; Transformmentioning
confidence: 99%
“…A post hoc trend decomposition analysis suggests that condom use behaviours may have shifted for YW as they entered martial partnerships (results not shown). Previous literature suggests that low condom use among AG and YW could be a product of failed negotiations fueled by low self-efficacy, relationship power and gender-inequitable norms and practices 6 18 43 60 61. Alternatively, condom use could have decreased due to changes in contraceptive use—such as moving from condoms to hormonal contraceptives—or desires to have children with their spouse 62–64.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that transactional sex can increase women’s HIV risk 19 20 41 65 66. To avert poverty, homelessness and food insecurity, some may turn to transactional sex to survive or to obtain desired commodities 17 18 67. AGYW’s economic disenfranchisement is characterised by a constellation of factors—including gendered discrimination and lack of social and business capital68—that make it difficult to AGYW to access the economic resources or earn a living wage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation